Gender-related differences in post-discharge bleeding among patients with acute coronary syndrome on dual antiplatelet therapy: A BleeMACS sub-study - Grodecki, Kajetan; Huczek, Zenon; Scisło, Piotr; Kowara, Michał; Raposeiras-Roubín, Sergio; D'Ascenzo, Fabrizio; Abu-Assi, Emad; Henriques, Jose Paulo Simao; Saucedo, Jorge; González-Juanatey, José Ramón; Wilton, Stephen B; Kikkert, Wouter J; et al. (Elsevier BV, 2018)
Bleeding is an independent risk factor of mortality in patients with acute coronary syndromes (ACS). BleeMACS project focuses on long-term bleeding events after hospital discharge, thus we evaluated gender-related differences in post-discharge bleeding among patients with ACS.
Keywords: Acute myocardial infarction; Antiplatelet agents; Platelet pharmacology; Cardiology